The unexpected discovery of the Mg(HMDS)2/MgCl2 complex as a magnesium electrolyte for rechargeable magnesium batteries1. Issue 11 (21st March 2015) - Liao, Chen; Sa, Niya; Key, Baris; Burrell, Anthony K.; Cheng, Lei; Curtiss, Larry A.; Vaughey, John T.; Woo, Jung-Je; Hu, Libo; Pan, Baofei; Zhang, Zhengcheng
<x xml:space="preserve">Abstract</x> We developed a unique class of non-Grignard, aluminum-free magnesium electrolytes based on a simple mixture of magnesium compounds: magnesium hexamethyldisilazide (Mg(HMDS)2) and magnesium chloride (MgCl2).